Effect of Basic Point-of-Care Ultrasound Course on Physicians’ Use in Clinical Practice: A Survey Study - Burcu Azapoğlu Kaymak; Merve Ekşioğlu; Özlem Dikme (İstanbul Medical Journal)
Introduction: To evaluate the impact of a basic point-of-care ultrasound (POCUS) course on physicians’ clinical use of POCUS in routine medical practice. Methods: This retrospective cross-sectional survey included physicians who attended one of 48 basic POCUS courses organized by the Emergency Medicine Association of Türkiye between 2019 and 2023. Among 610 physicians with available contact information, 201 completed the electronic survey, resulting in a response rate of 33%. The survey assessed participants’ demographics, previous ultrasound training, and self-reported changes in POCUS usage before and after the course. Results: The mean age of participants was 30.9±4.6 years, and 83.6% were emergency medicine specialists. A statistically significant increase in POCUS use was reported across all modalities following the course (p<0.001). The most prominent increases occurred in hepatobiliary (+58.8%), lower extremity deep vein thrombosis (+54.0%), and abdominal aorta (+50.8%) examinations. Use of POCUS for interventional procedures also rose substantially, particularly for lumbar puncture (+81.8%) and peripheral nerve blocks (+66.6%). Participants also reported enhanced diagnostic confidence, procedural competence, and integration of POCUS into decision-making. Conclusion: A short, structured POCUS course led to a meaningful increase in the clinical use of ultrasound across various diagnostic and interventional domains. Despite limitations such as recall bias and lack of follow-up assessment, the findings highlight the potential of focused training to improve practice patterns. Future course designs may benefit from incorporating certification components, objective structured clinical examination-style evaluations, and opportunities for supervised practice. Follow-up or refresher training may further support skill retention and long-term integration.